INTEGRATIVE FAITH DIGITAL PORTFOLIO ASSESSMENT (IFDPA): MODEL EVALUASI AUTENTIK PENDIDIKAN AGAMA KRISTEN DI ERA DIGITAL - Erna Setiyaningrum (Inculco Journal of Christian Education, 2026)
Penelitian ini bertujuan mengembangkan model Integrative Faith Digital Portfolio Assessment (IFDPA) sebagai kerangka evaluasi autentik Pendidikan Agama Kristen di era digital. Kajian ini dilatarbelakangi keterbatasan evaluasi konvensional yang cenderung menilai penguasaan kognitif, sedangkan dimensi refleksi iman, karakter, dan praktik hidup Kristen belum terukur secara sistematis. Penelitian menggunakan studi literatur konseptual dengan korpus 29 sumber terpilih, terdiri atas 24 artikel jurnal dan 5 buku atau kerangka akademik yang relevan dengan evaluasi autentik, e-portofolio, literasi digital, spiritual formation, dan Pendidikan Agama Kristen. Data dianalisis melalui analisis isi dan sintesis tematik. Hasil kajian merumuskan IFDPA sebagai model evaluasi yang memadukan empat komponen: authentic learning assessment, digital portfolio system, faith reflection component, serta character and spiritual formation. Kebaruan artikel ini terletak pada operasionalisasi model melalui bagan, alur implementasi, indikator artefak digital, dan rubrik penilaian refleksi iman serta karakter. IFDPA dapat digunakan guru PAK untuk menilai proses belajar, dokumentasi karya, refleksi teologis, dan aksi nyata peserta didik secara lebih holistik, formatif, dan kontekstual. This study aimed to develop the Integrative Faith Digital Portfolio Assessment (IFDPA) model as an authentic assessment framework for Christian Religious Education in the digital era. The study was driven by the limitation of conventional assessment, which tends to emphasize cognitive mastery while faith reflection, character development, and lived Christian practice are not assessed systematically. This conceptual literature review used a corpus of 29 selected sources, consisting of 24 journal articles and 5 academic books or frameworks related to authentic assessment, e-portfolios, digital literacy, spiritual formation, and Christian Religious Education. The data were analyzed through content analysis and thematic synthesis. The findings formulated IFDPA as an assessment model that integrates four components: authentic learning assessment, digital portfolio system, faith reflection component, and character and spiritual formation. The novelty of this article lies in the operationalization of the model through a diagram, implementation cycle, digital artifact indicators, and a rubric for assessing faith reflection and character formation. IFDPA can help Christian Religious Education teachers assess learning processes, digital evidence, theological reflection, and students’ real-life actions in a more holistic, formative, and contextual way.